ORGANIZING THE ACTIVITIES OF “MOBILE BRIGADES” OF SPECIALISTS TO PROVIDE MEDICAL CARE TO CHILDREN AND ADOLESCENTS, INCLUDING RURAL RESIDENTS - Yuldasheva F. U.; Rakhmatillayeva G. A.; Eshonkhodzhayeva M. O.; Abdulazizova D. Sh. (American Journals, 2024)
This article reveals questions about the organization of “mobile teams” of medical specialists to provide medical care to children and adolescents, including residents of rural areas, the article contains information about the purpose, objectives and basic principles of providing medical care to children in remote and hard-to-reach areas by mobile pediatric teams. The main directions of activity of mobile teams have been determined. An approximate equipment list is presented. The organizational forms of work of mobile teams with children, parents, the family of a sick child, and the involvement of parents in participating in medical work with their child are presented. The methodological recommendations are intended for health care managers, pediatricians and medical specialists.
Keywords: Pediatrician; consulting; autonomy; specialists; medicine; health care; mobile teams; health care; medical specialists; healthcare.